Electrical safety in low voltage distribution systems up to 1 000 V AC and 1 500 V DC. Equipment for testing, measuring or monitoring of protective measures. Effectiveness of residual current monitors (RCM) in TT, TN and IT systems Part 11, (26th September 2022) - British Standards Institution
No abstract available